(untitled) (International Journal of Nursing Education, 2022)
The objective of the study is to assess the knowledge of Neurological Examination furthermore to findout the mean difference between pre and post test score as well as association between the pre testlevel of knowledge and with their demographic variables. A pre-experimental study was conducted onNeurological Examination with 54 nursing students of Basic Bsc 3rd year in State college of nursing,107 Chander nagar Dehradun.. The Pre test data was collected by using self-administered questionnaireand mean was of (12.2.). The obtained data was analyzed using descriptive statistics. (Teaching wasgiven regarding anatomy and physiology of nervous system as well as OSPE conducted for neurologicalexamination. After 7 days of intervention post test was conducted for the same group of students andmean score was (16.8).SD of the pre and post test score was (2.9&1.91) and t test was done to findout the difference between pre and post test score. Calculated’ T ‘value is (5.9) and tabulated valueis 2.66. So findings are suggesting that calculated value is higher than tabulated value. It shows thatthe effectiveness of structured teaching on Neurological Assessment. Further there was associationof knowledge of neurological examination with their demographic variables and it was statisticallysignificant at p< o.o5 level. The study findings conclude that the student nurses had good knowledgeafter structured teaching programme regarding neurological examination.